2017
DOI: 10.1016/j.conbuildmat.2017.08.173
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of fibre-reinforced RPC columns under different loading conditions

Abstract: Behaviour of fibre-reinforced RPC columns under different loading conditions Behaviour of fibre-reinforced RPC columns under different loading conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…An experimental investigation was conducted by Hadi and Al-Tikrite [25] and Al-Tikrite and Figure 3 shows the details of the experimentally tested specimens. Table 1 presents the main test matrix of the experimental work conducted by…”
Section: Summary Of the Experimental Programmentioning
confidence: 99%
See 3 more Smart Citations
“…An experimental investigation was conducted by Hadi and Al-Tikrite [25] and Al-Tikrite and Figure 3 shows the details of the experimentally tested specimens. Table 1 presents the main test matrix of the experimental work conducted by…”
Section: Summary Of the Experimental Programmentioning
confidence: 99%
“…The influence of steel fibre on the axially loaded members such as reinforced RPC columns has been investigated by Hadi and Al-Tikrite [25] and Al-Tikrite and Hadi [26]. It was reported that the inclusion of steel fibres in the reinforced RPC columns has effectively influenced the load carrying capacity and the ductility of the columns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…e outcomes showed the hybridization between macrofiber and deformed fiber resulted in better ductility compared to only one kind of steel fiber addition or no fiber [19].…”
Section: Introductionmentioning
confidence: 99%